Instructing Malaysian Children with HFASD in English as a Second Language - A’ina Athirah Ahmad Sabri; Rabiah Tul Adawiyah Mohamed Salleh; Bruno Di Biase (Asiatic: IIUM Journal of English Language and Literature, 2021)
Autism awareness has recently increased globally, as evidenced by the increasing numbers of parents reported to be seeking advice on raising children with autism. In Malaysia, it is still unclear how children with autism spectrum disorder (ASD) acquire English in the ESL context. To shed some light on the issue, this paper examines how three high-functioning Malaysian children with ASD (HFASD) acquired English morphology, specifically the English plural structures from theDevelopmentally Moderated Focus-on-Form (DMFonF) instruction. DMFonF is an instructional approach introduced by Di Biase, which combines Pienemann’s Processability Theory developmental stages and Long’s Focus on Form feedback. Using DMFonF for sixteen weeks, the children were taught to produce English lexical and phrasal plural structures (noun + suffix- s and plural agreement within the NP) in the appropriate contexts. Data were collected at 4 points; T1 (week 5), T2 (week 9), T3 (week 13), and T4 (week 16). Results show that they acquired the English lexical and grammatical plurals taught in the DMFonF lessons faster than normally developing children did in past studies. The findings suggest that DMFonF not only effectively facilitates the acquisition of English lexicon but also activates grammatical development among children with ASD in the Malaysian context.